2012
DOI: 10.1002/cmdc.201200233
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Ultrasound and Light on Indocyanine‐Green‐Treated Tumour Cells and Tissues

Abstract: Photodynamic therapy (PDT) is emerging as a treatment modality for the management of neoplastic disease. Despite considerable clinical success, its application for the treatment of deep-seated lesions is constrained by the inability of visible light to penetrate deeply into tissues. An emerging alternative approach exploits the fact that many photosensitisers respond to ultrasound, eliciting cytotoxic effects on target cells and tissues; this has become known as sonodynamic therapy (SDT). The objectives of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
46
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 28 publications
3
46
0
3
Order By: Relevance
“…Hypertrophic scars not only affect the appearance and functions of skin, but also can result in psychological burdens for the patient. They are unique to humans and occur in response to surgery, trauma, burns, or other forms of dermal injury and inflammatory conditions, and do not regress spontaneously[2]. Clinically, they are characterized by massive scar formation, which invades normal adjacent skin and extends beyond the region of the initial wound.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertrophic scars not only affect the appearance and functions of skin, but also can result in psychological burdens for the patient. They are unique to humans and occur in response to surgery, trauma, burns, or other forms of dermal injury and inflammatory conditions, and do not regress spontaneously[2]. Clinically, they are characterized by massive scar formation, which invades normal adjacent skin and extends beyond the region of the initial wound.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, SDT, also named sonodynamic chemistry therapy (SDCT) [2] was used to treat hypertrophic scars on the surface of rabbit ears. On the basis of our previous studies, we combined the application of hematoporphyrin monomethyl ether (HMME) with SDT to explore the potential for synergistic treatment efficacy upon hypertrophic scars in rabbit ears.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] Studies have demonstrated that ICG can be activated by both light and ultrasound. 25 However, the applications of ICG are mainly hindered by some characteristics, including instability (aqueous instability, thermal degradation, and photodegradation), high protein binding (which leads to its rapid elimination from the body), lack of targeting, and its proneness to photobleaching. [26][27][28] An investigation of the new nanotechnology and drug delivery systems would bring hope to overcome these restrictions.…”
mentioning
confidence: 99%
“…These effects include the photo-and sonosensitizing activity of ICG, as well as the induction of PCI of chemotherapeutic agents on the basis of the amphiphilic nature of the molecule. In our own studies, we have demonstrated the cytotoxic and antitumour effect of intratumorally-injected ICG, in combination with laser light and low-intensity ultrasound [21]. The photo-and sonosensitizing effects of ICG, triggered by light and ultrasound irradiation, have been attributed to mitochondrial destruction that leads to the build-up of intracellular cytotoxic free radicals and subsequent cell death.…”
Section: Introductionmentioning
confidence: 94%